If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(-2) = 3(4) + -4(-2) + 2 Reorder the terms for easier multiplication: -2f = 3(4) + -4(-2) + 2 Multiply 3 * 4 -2f = 12 + -4(-2) + 2 Multiply -4 * -2 -2f = 12 + 8 + 2 Combine like terms: 12 + 8 = 20 -2f = 20 + 2 Combine like terms: 20 + 2 = 22 -2f = 22 Solving -2f = 22 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by '-2'. f = -11 Simplifying f = -11
| 5y/6=7/12 | | 0=x^10-2x^6+x^2 | | 12-(-2x+2)=0 | | 144=.5x+.75 | | (6x)(3x)=14000 | | 3xy+2yx= | | p(x)=x^10-2x^6+x^2 | | x^3y^2+y^2-56=0 | | 0=3x^2-21x+3 | | 1040=400x | | 2p+9p=11 | | tan45=13/x | | (3x-11)-3x=-13 | | 9=1+c | | 1/5x21/1 | | 3+a=7 | | ln(0.5x)= | | q+3=2q-23 | | 11/5x21/1 | | 3x=4(x-20) | | x+2x=30+5-0x | | 1/5x21 | | y^2-12y+6=0 | | 26+x=9 | | 12a+3=24d | | c-29=2c-77 | | x^2+xy+y^2-3=0 | | x*19=y | | 3x+7=-25-5x | | 2a-34=a-17 | | x+8x+1=100 | | 25=4x-11 |